Singapore : Financial Sector Assessment Program; Technical Note-Macroprudential Policy. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This technical note evaluates the macroprudential policy framework in Singapore with a focus on the price effect of macroprudential instruments. It assesses the domestic institutional arrangement, systemic risk monitoring framework, and macroprudential policy toolkit. The note assesses the strengths and weaknesses of the institutional arrangements for macroprudential policymaking and provides recommendations on how to enhance them further. It also describes the existing systemic risk monitoring framework and provides options to strengthen it. The use of macroprudential instruments in recent years and their effects on residential prices have also been discussed. The institutional framework for macroprudential policymaking has been revised and contains a clear mandate and well-defined objectives. The macroprudential mandate is assigned to dedicated committees within Monetary Authority of Singapore, limiting risk of dual mandates for the central bank. The authorities have taken important steps in recent years to develop the macroprudential policy framework and address relevant recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet